Implementation and Analysis of IEEE and ETSI Security Standards for Vehicular Communications - Fernandes, Bruno (2020)
Over the last years, there has been a considerable development in the field of wireless vehicular communications so as to satisfy the requirements of Cooperative Intelligent Transportation Systems (C-ITS). Standards such as IEEE 802.11p and ETSI ITS-G5 enable the so-called Vehicular Ad-Hoc Networks (VANETs). Vehicles can exploit VANETs to exchange information, such as alerts and awareness information, so as to improve drivers’ comfort and traffic efficiency. However, due to the expected popularity of ITS, VANETs could be prone to attacks by malicious sources. To prevent this, security standards, such as IEEE 1609.2 and ETSI ITS’ standards, were developed. In this work, the design and implementation of an API capable of conducting the required cryptographic algorithms and protocols for the transmission of secure messages according to the IEEE 1609.2 and ETSI ITS’ security standards are presented. The implemented security protocols are then integrated into a system emulating a public key infrastructure to evaluate the performance impact on safety-related communications, in particular, the delay associated with the communication’ coding/decoding process.